Challenges and Obstacles of Adoption BIM Technology in the Construction Industry in Iraq - Hamada, Hussein M.; Ahmad Tarmizi, Haron; Zahrizan, Zakaria; Humada, Ali M. (Universiti Malaysia Pahang, 2016)
Lack of application modern information technology in the construction sector in Iraq leads to complexity in understanding and interpreting diagrams and data, especially in large construction projects. Building Information Modeling (BIM) has a vital role in the construction industry through using the intelligent software by all of the specialists in the project team such as Architecture, civil engineer and MEP engineer. By using a new technique, BIM, can be determined and detect all the potential conflicts in design, construction and operation phases. A questionnaire has been designed to investigate perceptions related to BIM challenges and obstacles, besides to the desired benefits from using BIM technique. About 36 valid responses received from interested companies. The responses referred that BIM adoption in Iraqi construction industry was very low. There are many factors prevent or, at least, do not encourage the adoption of BIM technology in the construction industry. The most important factor is the cost of adoption the hardware and software related to the BIM technology and lack of request from owner.